Strategi Promosi Objek Wisata Pantai Matakus oleh Dinas Pariwisata Kabupaten Kepulauan Tanimbar Kecamatan Tanimbar Selatan - Moriolkosu, Jhon Rien; Rumra, Fatmawati (Department of Communication Science, University of Pattimura, 2024)
Abstract: This research is a qualitative descriptive research that aims to find out how the promotion strategy of the Tanimbar Islands Regency Tourism Office in promoting Matakus Beach. This research was carried out at the Tourism Office of Tanimbar Islands and Matakus Beach with data collection techniques in the form of observation, interviews, and also some documentation, as well as data analysis techniques using qualitative technique models according to Miles and Huberman consisting of data reduction, data presentation and conclusions. The results showed that the promotion strategy carried out by the Tanimbar Islands Regency Tourism Office in promoting matakus beach attractions was in accordance with the promotion mix theory. Where they use methods of Advertising, Sales Promotion, Direct Marketing, and Public Relations in promoting matakus beach. However, there are several methods that have not been used by the tourism office, namely personal sales and also the obstacles faced, namely costs and human resources that are still lacking in the tourism office so that the methods used have not run effectively. But in the future the tourism office will update it all so that the promotion of matakus beach attractions can run well.